Acute and Chronic Toxicity of Soluble Fractions of Industrial Solid Wastes on Daphnia magna and Vibrio fischeri. (18th January 2012) - Flohr, Letícia; Castilhos Júnior, Armando Borges de; Matias, William Gerson
Abstract : Industrial wastes may produce leachates that can contaminate the aquatic ecosystem. Toxicity testing in acute and chronic levels is essential to assess environmental risks from the soluble fractions of these wastes, since only chemical analysis may not be adequate to classify the hazard of an industrial waste. In this study, ten samples of solid wastes from textile, metal-mechanic, and pulp and paper industries were analyzed by acute and chronic toxicity tests with Daphnia magna and Vibrio fischeri . A metal-mechanic waste (sample MM3) induced the highest toxicity level to Daphnia magna (CE 50, 48 h = 2.21 %). A textile waste induced the highest toxicity level to Vibrio fischeri (sample TX2, CE 50, 30 min = 12.08 %). All samples of pulp and paper wastes, and a textile waste (sample TX2) induced chronic effects on reproduction, length, and longevity of Daphnia magna . These results could serve as an alert about the environmental risks of an inadequate waste classification method.